2003
DOI: 10.1046/j.1469-0691.2003.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of telithromycin (HMR 3647) against Greek Streptococcus pyogenes and Streptococcus pneumoniae clinical isolates with different macrolide susceptibilities

Abstract: The susceptibilities to macrolides and telithromycin of 161 Streptococcus pyogenes and 145 Streptococcus pyogenes strains, consecutively isolated from five Greek hospitals, were determined by Etest. Moreover, mechanisms of resistance to macrolides were phenotypically and genetically determined by double disk induction test and PCR, respectively. Of the S. pneumoniae and S. pyogenes isolates, 42.8% and 30.8%, respectively, were found to be resistant to erythromycin. Of the erythromycin-resistant S. pneumoniae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
1
8
1
2
Order By: Relevance
“…Ten percent resistance to erythromycin was reported by the PROTEKT investigators, with the highest rates noted in Poland (42%), Hong Kong (28%), Italy, Portugal and Spain (all > 20%) [11]. Several other smaller studies have reported macrolide resistance rates that are similar to our results: 2.5% in Great Britain and Ireland [12], 10% in central and eastern Europe [13], 31% in Greece [14], 78% in Taiwan [15], 14% in South Africa [10], 30% in Spain [16], and 14% in Germany [17].…”
Section: Discussionsupporting
confidence: 89%
“…Ten percent resistance to erythromycin was reported by the PROTEKT investigators, with the highest rates noted in Poland (42%), Hong Kong (28%), Italy, Portugal and Spain (all > 20%) [11]. Several other smaller studies have reported macrolide resistance rates that are similar to our results: 2.5% in Great Britain and Ireland [12], 10% in central and eastern Europe [13], 31% in Greece [14], 78% in Taiwan [15], 14% in South Africa [10], 30% in Spain [16], and 14% in Germany [17].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, and with respect to the MLS B phenotype, the CR phenotype and the ermB gene is most frequently detected among the S. pneumoniae MLS B clinical isolates [21] (N.J. Legakis, unpublished results), whereas the IR phenotype and the class A erm gene seems to be more prevalent among the S. pyogenes MLS B clinical isolates [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Infatti, è necessario avvalersi di una strategia terapeutica che escluda l'impiego di tutti gli antibiotici facenti parte del gruppo MLSB nel caso di isolamento di pneumococchi con fenotipi cMLSB ed iMLSB i quali presentano una resistenza allargata nei confronti di tutto lo spettro delle molecole appartenenti a questo gruppo. Al contrario, l'utilizzo di un macrolide a 16 atomi (josamicina e rokitamicina) o di un ketolide (telitromicina) è suggerito qualora vengano isolati ceppi di S. pneumoniae con fenotipo a pompa di efflusso in quanto notoriamente resistenti ai macrolidi a 14 e 15 atomi (7,10,15).…”
Section: Conclusioniunclassified